THE USE OF PRODUCTION WASTES FRACTIONS FOR PRODUCTION OF FUNCTIONAL COATINGS BY WELDING OF HFC - E. F. Panteleenko; G. A. Petryshyn (Литьë и металлургия)
Possibility and reasonability of application of self-fluxing diffusion- alloyed powders from the fraction production wastes for obtaining of coverings by welding method by currents of high frequency are considered. The structure and properties of the received coverings is investigated.